Materials Chemistry - Fraser, Sean, editor (Forest Hills, NY : Willford Press, 2018)
The process of designing and discovering new materials is known as materials chemistry. It is a sub-field of materials sciences and is very important in the present age. The important aspects covered under this field are structure, which includes nanostructure, atomic structure, macro structure, crystallography, bonding, etc. Some of the main materials studied under this field are polymers, ceramic materials, composites, metal alloys, etc. This book is compiled in such a manner, that it will provide in-depth knowledge about the theory and practice of materials chemistry. The topics covered herein deal with the core subjects of the area. This textbook is a complete source of knowledge on the present status of this important field.